Analysis of the best roughness surface based on the bearing area curve theory. (March 2022) - He, Peiyu; Lu, Suwen; Wang, Yun; Li, Ruitao; Li, Fuzhu
An in-depth study of friction and wear requires analysis of the surface morphologies and contact status of friction pairs in mechanical systems. The bearing area curve is introduced for the calculation of wear, and combined with the concept of repositioning. The application of fast calculation of wear amount and improved three-dimensional characterization of a bearing area curve is achieved by this new method. The best roughness surface is used as the target surface to extract the target bearing area curve. The influence of microtexture parameters on the bearing area curve is studied to determine the optimal microtexture parameters. The test results show that a matching texture surface has a short run-in time and the lowest friction coefficient after stabilization among the surfaces studied herein, and the presence of a texture changes the wear mechanism from the original adhesive wear to abrasive wear and improves the tribological performance. The best texture parameters and laser process parameters are determined, which provide new ideas for the optimal design of surface topography.